2020
DOI: 10.3390/antiox9111089
|View full text |Cite
|
Sign up to set email alerts
|

HR-LCMS-Based Metabolite Profiling, Antioxidant, and Anticancer Properties of Teucrium polium L. Methanolic Extract: Computational and In Vitro Study

Abstract: In this study, we investigate the phytochemical profile, anticancer, and antioxidant activities of Teucrium polium methanolic extract using both in vitro and in silico approaches. The results showed the identification of 29 phytochemical compounds belonging to 13 classes of compounds and 20 tripeptides using High Resolution-Liquid Chromatography Mass Spectrometry (HR-LCMS). 13R-hydroxy-9E,11Z octadecadienoic acid, dihydrosamidin, valtratum, and cepharantine were the main compounds identified. The tested extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 92 publications
(107 reference statements)
3
36
0
Order By: Relevance
“…It has been reported that T. polium compounds have anti-profilative, anti-diabetic, anticancer, and pro-apoptotic activities [ 15 , 29 ]. Recently, a lot of studies, focusing on the biological and pharmacological activity of plants in folk medicine, including the plant of Teucrium polium L., mostly have indicated significant differences in chemical composition (total flavonoids, total phenolic contents) and biological activity due to differences in the geographical location of the plant material but not differences due to its phenological stage [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that T. polium compounds have anti-profilative, anti-diabetic, anticancer, and pro-apoptotic activities [ 15 , 29 ]. Recently, a lot of studies, focusing on the biological and pharmacological activity of plants in folk medicine, including the plant of Teucrium polium L., mostly have indicated significant differences in chemical composition (total flavonoids, total phenolic contents) and biological activity due to differences in the geographical location of the plant material but not differences due to its phenological stage [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several examples of plant-based drugs include nicotine (antimicrobial), nordihydroguaiaretic acid (antioxidant), vinblastine (anticancer), aescin (anti-inflammatory), acetyldigoxin (cardiotonic), l -dopa (antiparkinsonism), etc. In spite of the discovery of innumerable drugs of plant origin, the exploration of novel bioactive compounds is yet requisite to enhance the range access and to search less toxic and more efficacious drugs [ 4 , 5 , 6 ]. Medicinal and economic importance of higher plants, specifically angiosperms, has been explored thoroughly.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, attention has been shifted toward traditional and alternative medicines or foodderived products rich in antidiabetic phytoconstituents. The bioactive components present in plants and plants derived products such as alkaloids, flavonoids, glycosides, gum, carbohydrates, triterpenes, and different types of peptides are usually responsible for their therapeutic importance [18][19][20][21]. Recently, okra has been recognized for its potential therapeutic purposes due to the presence of various important phytochemicals including polysaccharides [1,22].…”
Section: Introductionmentioning
confidence: 99%